Transgene expression knock-down in recombinant Modified Vaccinia virus Ankara vectors improves genetic stability and sustained transgene maintenance across multiple passages - Neckermann, Patrick; Mohr, Madlen; Billmeier, Martina; Karlas, Alexander; Boilesen, Ditte R.; Thirion, Christian; Holst, Peter J.; Jordan, Ingo; Sandig, Volker; Asbach, Benedikt; Wagner, Ralf (Frontiers in Immunology, 2024)
Modified vaccinia virus Ankara is a versatile vaccine vector, well suited for transgene delivery, with an excellent safety profile. However, certain transgenes render recombinant MVA (rMVA) genetically unstable, leading to the accumulation of mutated rMVA with impaired transgene expression. This represents a major challenge for upscaling and manufacturing of rMVA vaccines. To prevent transgene-mediated negative selection, the continuous avian cell line AGE1.CR pIX (CR pIX) was modified to suppress transgene expression during rMVA generation and amplification. This was achieved by constitutively expressing a tetracycline repressor (TetR) together with a rat-derived shRNA in engineered CR pIX PRO suppressor cells targeting an operator element (tetO) and 3’ untranslated sequence motif on a chimeric poxviral promoter and the transgene mRNA, respectively. This cell line was instrumental in generating two rMVA (isolate CR19) expressing a Macaca fascicularis papillomavirus type 3 (MfPV3) E1E2E6E7 artificially-fused polyprotein following recombination-mediated integration of the coding sequences into the DelIII (CR19 M-DelIII) or TK locus (CR19 M-TK), respectively. Characterization of rMVA on parental CR pIX or engineered CR pIX PRO suppressor cells revealed enhanced replication kinetics, higher virus titers and a focus morphology equaling wild-type MVA, when transgene expression was suppressed. Serially passaging both rMVA ten times on parental CR pIX cells and tracking E1E2E6E7 expression by flow cytometry revealed a rapid loss of transgene product after only few passages. PCR analysis and next-generation sequencing demonstrated that rMVA accumulated mutations within the E1E2E6E7 open reading frame (CR19 M-TK) or deletions of the whole transgene cassette (CR19 M-DelIII). In contrast, CR pIX PRO suppressor cells preserved robust transgene expression for up to 10 passages, however, rMVAs were more stable when E1E2E6E7 was integrated into the TK as compared to the DelIII locus. In conclusion, sustained knock-down of transgene expression in CR pIX PRO suppressor cells facilitates the generation, propagation and large-scale manufacturing of rMVA with transgenes hampering viral replication.